2005
DOI: 10.1145/1057237.1057243
|View full text |Cite
|
Sign up to set email alerts
|

Predicting human interruptibility with sensors

Abstract: A person seeking another person's attention is normally able to quickly assess how interruptible the other person currently is. Such assessments allow behavior that we consider natural, socially appropriate, or simply polite. This is in sharp contrast to current computer and communication systems, which are largely unaware of the social situations surrounding their usage and the impact that their actions have on these situations. If systems could model human interruptibility, they could use this information to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
215
1
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(224 citation statements)
references
References 22 publications
3
215
1
5
Order By: Relevance
“…Studies have shown that human interruption in offices can be captured accurately by simple sensors such as these [6,9], and other studies have found that users decide whether to answer their phones based on their activity, location, and who is callingall of which are becoming more observable using current phone sensors [7,15,16]. With new applications to classify interruption preferences and react based on these predictions, it is not clear what accuracy level is acceptable for users.…”
Section: Related Workmentioning
confidence: 99%
“…Studies have shown that human interruption in offices can be captured accurately by simple sensors such as these [6,9], and other studies have found that users decide whether to answer their phones based on their activity, location, and who is callingall of which are becoming more observable using current phone sensors [7,15,16]. With new applications to classify interruption preferences and react based on these predictions, it is not clear what accuracy level is acceptable for users.…”
Section: Related Workmentioning
confidence: 99%
“…Such understanding about others allows behavior that is considered natural, socially appropriate, or simply polite. As Fogarty et al [5] have identified the fact half a decade ago, current computer and communication systems are still largely unaware of the social situations surrounding their usage and the impact that their actions have on these situations. There have been several research attempts, but there is not much development in this regards.…”
Section: Related Workmentioning
confidence: 99%
“…Informal communication between coworkers is considered as an optimal way to exchange rapid feedback, share local context and reference common depictions [2]. But it comes at a cost: interruptions.…”
Section: Introductionmentioning
confidence: 99%
“…However, once initiated at right times they serve as natural breaks and provide content for expressive interaction between colleagues. Current solutions supporting handling interruptions assume the interruptee's availability to be the best predictor of an appropriate interruption moment [2]. Yet, interruptors seem not to fully adhere to those availability indications as the proposed systems fail to help them convey their communicative needs.…”
Section: Introductionmentioning
confidence: 99%